First‐Principles Study on Interfacial Bonding Characteristics and Tensile Deformation Behavior of Ni (001)/Ni3Al (001) in K418 Superalloy. Issue 2 (25th December 2022) - Wang, Qin; Liu, Furong; Lin, Xin; Song, Jinxia; Feng, Haoyuan
Abstract: In order to theoretically explore the interfacial bonding properties between the main phase (γ) and the second precipitated phase (γ') in K418 superalloy formed by direct laser deposition. First‐principles calculation is utilized to study the adhesion work, interfacial energy, electronic structure, bonding properties, and tensile properties between γ phase (Ni (001)) and γ' phase (Ni3 Al (001)). The results show that the interface energy of the NiAl‐center (0.35–1.19 J m −2 ) is the smallest and therefore it is with the highest interface bonding strength. The electronic analysis suggests that strong Ni‐Al covalent and ionic bonds as well as Ni‐Ni metal bonds at the interface of the NiAl‐center model are formed with the appearance of obvious orbital hybridization. The yield strength of the NiAl‐top model reaches up to 19.38 GPa under the uniaxial tensile test, which is further increased when doped with those atoms of Re, Ta, and W, up to 20.38, 20.42, and 20.93 GPa, respectively. A fundamental understanding is presented here for the design of superalloys. Abstract : The adhesion work, interface energy, and bonding properties of four models of the Ni(001)/Ni3 Al(001) are explored. NiAl‐center is the most stable among the four models. The tensile behavior of three doped atoms (Re, Ta, and W) in the NiAl‐top is studied with the consideration of the Poisson contraction.